Workshop on TPACK-Based Differentiated Learning in Reading and Writing Skills - Dewi Nur Widiyati; Dwiyani Pratiwi; Yuyun Yulia; Wipsar Siwi Dona Ikasari (Universitas Pendidikan Ganesha, 2025)
The rapid development of information technology has transformed the characteristics of students from the millennial generation to Generation Z. This shift requires teachers to design learning that not only focuses on content but also fosters creativity and 21st-century skills. This study aims to evaluate the effectiveness of training programs in enhancing teachers' ability to implement differentiated instruction based on Technological Pedagogical Content Knowledge (TPACK) in reading and writing skills. The research employed a quantitative approach with a pre-experimental design using the one-group pretest-posttest model. The research subjects consisted of 41 participants, including teachers and school principals, selected through purposive sampling. Data were collected through observation, interviews, and documentation, using observation sheets and interview guides as instruments. The collected data were analyzed using qualitative thematic analysis. The results showed a significant improvement in teachers' understanding of integrating technology and pedagogy into differentiated learning. Teachers were able to design adaptive, interactive, and student-responsive literacy instruction. The findings underscore the importance of TPACK-based training in strengthening teachers’ competencies to meet the demands of 21st-century education. The study implies the need to reinforce TPACK-based training programs as a strategy to improve teacher professionalism.